Correlation between Self-Talk and Emotional Regulation Among Student Volleyball Athletes - Amelia Musyarofah; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aims to determine the relationship between self-talk and emotion regulation in volleyball student athletes.